2007
DOI: 10.1002/cncr.23101
|View full text |Cite
|
Sign up to set email alerts
|

Serum carcinoembryonic antigen level is associated with epidermal growth factor receptor mutations in recurrent lung adenocarcinomas

Abstract: BACKGROUND. The presence of epidermal growth factor receptor (EGFR) gene mutations is a good indicator of the clinical efficacy of gefitinib in patients with nonsmall cell lung cancer. It was recently reported that the serum carcinoembryonic antigen (CEA) level could be a predictive factor for the efficacy of gefitinib treatment; therefore, it is suggested that the EGFR gene mutation is associated with the serum CEA level. The current study analyzed the association between EGFR gene mutations and clinical feat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

8
28
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(36 citation statements)
references
References 30 publications
8
28
0
Order By: Relevance
“…Both the univariate and multivariate analyses indicated that the serum CEA levels correlated with EGFR mutations (higher serum CEA levels were associated with higher EGFR gene mutation rates). Our data are similar to the findings of Okamato et al [34]. Shoji et al [35] reported that the rate of EGFR gene mutation significantly increased as the serum CEA levels increased (for serum CEA levels <5, ≥5 (but <20), and ≥20, the rates of EGFR gene mutation were 35, 55 and 87.5%, respectively; p  = 0.040).…”
Section: Discussionsupporting
confidence: 91%
“…Both the univariate and multivariate analyses indicated that the serum CEA levels correlated with EGFR mutations (higher serum CEA levels were associated with higher EGFR gene mutation rates). Our data are similar to the findings of Okamato et al [34]. Shoji et al [35] reported that the rate of EGFR gene mutation significantly increased as the serum CEA levels increased (for serum CEA levels <5, ≥5 (but <20), and ≥20, the rates of EGFR gene mutation were 35, 55 and 87.5%, respectively; p  = 0.040).…”
Section: Discussionsupporting
confidence: 91%
“…Our data are similar to the data of Okamato et al (11). Shoji et al (22) reported that the rate of the EGFR gene mutation significantly increased as the serum CEA level increased (for serum CEA levels of <5, ≥5 but <20, and ≥20, the rate of the EGFR gene mutation was 35, 55 and 87.5%, respectively; P=0.040). However, our data showed that the status of the EGFR mutation made no difference in the CEA levels.…”
Section: Discussionsupporting
confidence: 91%
“…On the other hand, Okamoto et al (24) and Jung et al (23) reported that patients treated with EGFR-TKI with higher CEA levels had a longer survival and a better response than those with low CEA levels. Shoji et al (36) reported that the rate of EGFR gene mutation is significantly increased as the levels of CEA increases (for the levels of CEA of <5, ≥5 but <20 and ≥20 the rate of EGFR gene mutation was 35, 55 and 87.5%, respectively; P=0.040). Their study presented a significant association between EGFR gene mutations and the levels of CEA in patients with lung adenocarcinomas.…”
Section: Discussionmentioning
confidence: 99%